Ternary Planar Heterojunction Organic Solar Cells Based on the Ternary Active Layers: α-6T/AlPcCl/C60 - Hajar Ftouhi; Hind Lamkaouane; Mustapha Diani; Guy Louarn; Ludovic Arzel; Jean-Christian Bernède; Mohammed Addou; Linda Cattin (Solar, 2022)
Ternary planar heterojunction organic solar cells (PHJ-OPVs) were fabricated using three organic small molecules, alpha-sexithiophene (α-6T), aluminum phthalocyanine chloride (AlPcCl) and fullerene (C60). These molecules can be easily sublimated under a vacuum; they have complementary optical absorption spectra and their energy band structure alignment is favorable for electronic charge transfers. Moreover, α-6T and AlPcCl have almost the same HOMO, which is desirable to avoid any decrease in open circuit voltage. The AlPcCl intercalated layer bridges the energy levels of the electron donor, α-6T, and the electron acceptor, C60, which facilitates charge transport through the energy cascade effect. Moreover, the charge carrier mobility measurements of AlPcCl, using the space charge limited current method, demonstrated that it iss ambipolar. All these properties combine to improve the power conversion efficiency (PCE) of PHJ-OPVs by moving from binary structures (α-6T/C60, α-6T/AlPcCl and AlPcCl/C60) to ternary ones (α-6T/AlPcCl/C60). We show, in this study, that both interfaces of the ternary PHJ-OPVs are efficient for carrier separation. After optimization of the different layer thickness, we show that, by comparing the optimum efficiencies of the binary PHJ-OPVs, the realization of ternary PHJ-OPVs, based on the active layers α-6T/AlPcCl/C60, using the following optimized method, allows us to achieve a PCE of 4.33%.